Catheter Ablation of Ventricular Tachycardia as the First‐Line Therapy in Patients With Coronary Artery Disease and Preserved Left Ventricular Systolic Function: Long‐Term Results. (17th August 2015) - CLEMENS, MARCELL; PEICHL, PETR; WICHTERLE, DAN; PAVLŮ, LUDĚK; ČIHÁK, ROBERT; ALDHOON, BASHAR; KAUTZNER, JOSEF
VT Ablation in Patients With Preserved LV Function Introduction Patients with coronary artery disease (CAD), relatively preserved left ventricular ejection fraction (LVEF), and hemodynamically tolerated ventricular tachycardia (VT) may benefit from catheter ablation as the first‐line treatment. Our aim was to analyze the long‐term results of VT ablation in this population. Methods and Results Thirty‐one patients (1 woman, mean age 67 ± 10 years) with CAD, tolerated VT, and LVEF ≥40% underwent catheter ablation as the first‐line treatment of the arrhythmia. Catheter ablation was performed in order to abolish all inducible VTs. An ICD was implanted if sustained VT of any morphology remained inducible after the procedure. The mean LVEF was 48 ± 6% and the mean VT cycle length reached 348 ± 70 milliseconds in the study cohort. Clinical and all inducible VTs were abolished in 90% (28/31) and 58% (18/31) of the patients, respectively. An ICD was subsequently implanted in 42% of cases. Over a mean follow‐up of 3.8 ± 2.9 years, 42% (13/31) patients died. Survival of the patients with or without the ICD was not significantly different (P = 0.47). VT recurrence was observed in 11% (2/18) of patients who had complete elimination of all inducible VTs. No sudden death occurred in patients without the ICD. Conclusions Catheter ablation of VT as the first‐line treatment in patients with CAD and relatively preserved LVEF is a viable strategy. It may prevent implantation of the ICD in a considerable proportion of patients. Abolition of all inducible VTs confers low VT recurrence rate over a long‐term follow‐up.